Assessing China's Residential Real Estate Market - Ding, Ding (IMF Working Papers; Working Paper ;, 2017)
China's real estate market rebounded sharply after a temporary slowdown in 2014-2015. This paper uses city-level data to estimate the range of house price overvaluation across city-tiers and assesses the main risks of a sharp housing market slowdown. If house prices rise further beyond 'fundamental' levels and the bubble expands to smaller cities, it would increase the likelihood and costs of a sharp correction, which would weaken growth, undermine financial stability, reduce local government spending room, and spur capital outflows. Empirical analysis suggests that the increasing intensity of macroprudential policies tailored to local conditions is appropriate. The government should expand its toolkit to include additional macroprudential measures and push forward reforms to address the fundamental imbalances in the residential housing market.